Efeito do treino de marcha em esteira e com realidade virtual sobre o equil??brio e marcha de indiv??duos com doen??a de Parkinson: ensaio cl??nico controlado aleatorizado cego - Melo, Gileno Edu Lameira de (2017)
Objective: Determine the effect of gait training with virtual reality in comparison to over ground training and treadmill training on balance and gait in individuals with Parkinson???s disease. Material and Methods: Study I: A systematic review was performed of articles published between 2011 and 2016 retrieved from four databases using the following keywords and synonyms: Parkinson???s Disease, Gait, and Virtual Reality Exposure Therapy. Study II: Detailed description of the study protocol. Study III: A population-based sample was composed of 37 individuals with Parkinson???s randomly allocated to three groups (control, treadmill and virtual reality). The participants were evaluated on four occasions: pre-intervention; immediately after first intervention session; post-intervention; and one month after last intervention session). Evaluations involved the administration of the Hoehn & Yahr scale, the motor section of the Unified Parkinson???s Disease Rating Scale and Parkinson ???s disease Questionnaire (PDQ-39 for the evaluation of quality of life). Long-distance walking was evaluated using the Six-Minute Walk Test with the aid of the G-WALK (BTS) inertial sensor and monitoring of heart rate, blood pressure and perceived exertion (modified Borg scale). Training was performed in 20-minute sessions at a frequency of three sessions per week for four weeks. Study IV: Thirty-seven individuals with Parkinson???s were allocated to a control group, treadmill group and Xbox group Training in each group was performed in 12 sessions. The participants were evaluated on four occasions: pre-intervention; immediately after first training session; after 12 sessions; and one month after last training session). The evaluations involved the administration of the Hoehn & Yahr scale, the motor section of the Unified Parkinson???s Disease Rating Scale, Parkinson???s Disease Questionnaire (PDQ-39 for the evaluation of quality of life), the Berg Balance Scale, and the Tinetti Test. For the evaluation of spatiotemporal gait variables, the Timed Up and Go test was performed using the G-WALK (BTS) inertial sensor. Results: Study I: Twenty-one studies with a methodological quality of 5 or more points on the PEDro scale were analyzed and the review was published in the journal Archives of Neuropsychiatry. Study II: Protocol study published in the journal Manual Therapy. Study III: Significant improvements in the distance travelled and velocity on the Six-Minute Walk Test were found in the virtual reality and treadmill groups in comparison to the control group (p < 0.05), whereas no significant differences were found between the virtual reality and treadmill groups. Study IV: Improvements in the Berg Balance Scale, Tinetti balance and cognition subscales and mobility domain of the PDQ-39 were found in the treadmill and Xbox groups in comparison to the control group. Conclusion: The results of Studies III and IV suggest that, when used with the aim of improving mobility, balance and spatiotemporal gait variables in individuals with Parkinson???s disease, training with virtual reality is as effective as treadmill training.